Neural Correlates of Distorted Self-concept in Individuals With Internet Gaming Disorder: A Functional MRI Study - Kim, Min-Kyeong; Jung, Young Hoon; Kyeong, Sunghyon; Shin, Yu-Bin; Kim, Eunjoo; Kim, Jae-Jin (Frontiers in Psychiatry, 2018)
Background and aims Discrepancy between ideal self-guide and actual self-concept evoke dejection-related feeling, and often individuals with internet gaming disorder (IGD) use games as the tool to escape those negative emotions. The aim of this study was to evaluate the pattern of self-discrepancy based on actual and ideal self-images and elucidate the neural correlates underlying the distorted self in individuals with IGD. Methods Nineteen male individuals with IGD and 20 healthy controls (HCs) underwent functional magnetic resonance imaging where they decided on whether they agreed with the adjectives describing their actual or ideal self on a four-point Likert Scale. Two-sample t-test on the self-discrepancy contrast was conducted for neuroimaging analysis and correlation analysis was performed between the behavioral data and regional activities. Results The IGD group evaluated both their ideal self and actual self more negatively than the HC group. Actual self-concept was associated with satisfaction with psychological needs as opposed to ideal self-guide. Brain activity in the inferior parietal lobule was significantly decreased in individuals with IGD relative to HCs in the self-discrepancy contrast. In addition, neural activity during evaluating actual self-concept showed a significant group difference. Conclusion These results provide novel evidence for distorted self-concept of people with IGD. Individuals with IGD had a negative ideal and actual self-image. Neurobiologically, dysfunction in the inferior parietal lobule associated with emotional regulation and negative self-evaluation was found in IGD. Considering the characteristics of IGD that often develop in adolescence, this self-concept problem should be noted and applied with appropriate therapy.